A Series of Benzylidenes Linked to Hydrazine‐1‐carbothioamide as Tyrosinase Inhibitors: Synthesis, Biological Evaluation and Structure−Activity Relationship. Issue 8 (3rd August 2020) - Hosseinpoor, Hona; Iraji, Aida; Edraki, Najmeh; Pirhadi, Somayeh; Attarroshan, Mahshid; Khoshneviszadeh, Mahsima; Khoshneviszadeh, Mehdi
Abstract: Tyrosinase is a type 3 copper enzyme responsible for skin pigmentation disorders, skin cancer, and enzymatic browning of vegetables and fruits. In the present article, 12 small molecules of 2‐benzylidenehydrazine‐1‐carbothioamide were designed, synthesized and evaluated for their anti‐tyrosinase activities followed by molecular docking and pharmacophore‐based screening. Among synthesized thiosemicarbazone derivatives, one compound, (2 E )‐2‐[(4‐nitrophenyl)methylidene]hydrazine‐1‐carbothioamide, is the strongest inhibitor of mushroom tyrosinase with IC50 of 0.05 μM which demonstrated a 128‐fold increase in potency compared to the positive control. Kinetic studies also revealed mix type inhibition by this compound. Docking studies confirmed the complete fitting of the synthesized compounds into the tyrosinase active site. The results underline the potential of 2‐benzylidenehydrazine‐1‐carbothioamides as potent pharmacophore to extend the tyrosinase inhibition in drug discovery. Abstract :